Decolonizing Character Representation: A Postcolonial Analysis of Race-Swapping in Disney’s The Little Mermaid Movie (2023) - Tano, Andreas; Simanjuntak, Immanuel Sheva (Jurnal Pendidikan Makarios, 2024)
This article investigates the implications of race-swapping character representation in the 2023 live-action adaptation of Disney's "The Little Mermaid," focusing on the casting of Halle Bailey, a Black actress, as Ariel. Utilizing postcolonial criticism frameworks, particularly Robert J.C. Young's theories, this study explores the historical and cultural significance of this casting decision. The findings suggest that the movie's approach to race-swapping serves as a means to challenge and redefine traditional racial narratives within popular media. The research identifies three primary outcomes: 1) Reimagining racial roles is exemplified in the movie by the casting of a Black actress in a traditionally white role disrupts conventional racial representations, prompting viewers to reconsider the historical association of race with specific characters and roles. 2) The race-swapping encourages viewers a re-evaluation of historical narratives in the story, deepening the audience's understanding and allowing for a more inclusive perspective of the past of different racial groups. 3) Upon promoting racial inclusivity and diversity, the movie strives to prioritize the significance of acknowledging the historical experiences of the marginalized societies in an effort not to be forgotten or eliminated. The movie approach leads to dual perspectives and biases: promoting inclusivity while also at the same time reimagining historical issues related to race. Consequently, this study highlights the importance of critically engaging with media representations to foster a more inclusive and representative cultural landscape by examining its historical biases. The movie's innovative approach to character representation encourages the need for ongoing dialogue about the intersections of race, history, and societal roles in contemporary media​.